Comparative assessment between different sample preparation methodologies for PTGA CO adsorption assays—Pellet, powder, and fragment samples - Alessandro da S Ramos; Gabriel E de Araujo; Leonardo Siviero; João MM Ketzer; Roberto Heemann; Rogerio V Lourega; Luiz F Rodrigues (Adsorption Science & Technology)
The carbon dioxide sorption process at coal seams is very important for understanding the trapping mechanisms of carbon capture and storage. The gas retention capacity of coal seams can be estimated using indirect methods based on the adsorption/desorption isotherms obtained in the laboratory. However, the gas sorption capacity can be overestimated or underestimated depending on the sample preparation. This work evaluates different sample preparations and their theoretical adsorption capacity using coal samples from the Cambui coal field (Parana Basin), southern Brazil. Experiments using a thermogravimetric balance were done to calculate the theoretical adsorption capacity, while sample characterization was done through immediate analysis, elementary analysis, and mineralogical studies. The sample preparations used in this work were powder, pellets, and fragments. While the powder form presents an average behavior, without any experimental complication, the pellet is extremely sensitive to any variation in the sample preparation, such as fractures, and the fragment requires a much longer experiment time than the other sample preparations, being impracticable for some cases.